Beam based alignment of the SSRF storage ring - 张满洲 李浩虎 姜伯承 刘桂民 李德明 (Chinese physics C, 2009)
There are 140 beam position monitors （BPMs） in the Shanghai Synchrotron Radiation Facility （SSRF） storage ring used for measuring the closed orbit. As the BPM pickup electrodes are assembled directly on the vacuum chamber, it is important to calibrate the electrical center offset of the BPM to an adjacent quadrupole magnetic center. A beam based alignment （BBA） method which varies individual quadrupole magnet strength and observes its effects on the orbit is used to measure the BPM offsets in both the horizontal and vertical planes. It is a completely automated technique with various data processing methods. There are several parameters such as the strength change of the correctors and the quadrupoles which should be chosen carefully in real measurement. After several rounds of BBA measurement and closed orbit correction, these offsets are set to an accuracy better than 10 μm. In this paper we present the method of beam based calibration of BPMs, the experimental results of the SSRF storage ring, and the error analysis.